CFD investigation of methane combustion with excess air in can-type gas turbine combustor - Md Shamsuzzaman Zahir; Hasril Hasini; Nur Irmawati Om; Byan Wahyu Riyandwita; Norfadilah Mansyur (Penerbit Universiti Kebangsaan Malaysia, 2024)
This paper presents an investigation on the effect of excess air to combustion characteristics in a full-scale, gas turbine combustor, commonly used in power plant. The investigation was carried out using Computational Fluid Dynamics (CFD), and prior validation was made with the actual operation data of a power station, as well as the adiabatic flame temperature of methane. The mass fraction of CO2, O2 and NOx emissions for blended methane with different percentages of excess air explosions was also investigated. The stoichiometric excess air varies from 0% to 30% with air-fuel mixture of 2.7 kg/s. The geometric model of the combustor is extracted from actual gas turbine combustor using 3D scanner and converted into CAD model for simulation. The Navier-Stokes equations were solved using commercial CFD code, ANSYS Fluent, with RNG k-ε chosen to close the turbulence. For reacting species, the species transport model is assumed. Results showed that the addition of excess air during combustor has little effect on the velocity and temperature distribution, both at the combustor interior, as well as at the exit. For the emission of CO2 and O2, though there was no clear trend on the relations between the emission of these species and the excess air, the impact was quite significant. The production of NOx was also found to be independent on the excess air ratio, but instead, was a strong function of combustion and exhaust gas temperature.